RESPON PERTUMBUHAN DAN HASIL TIGA VARIETAS SAWI HIJAU (Brassica juncea L.) TERHADAP PENAMBAHAN PUPUK KOTORAN SAPI PADA LAHAN KERING - Usmadi, Usmadi; Kasanah, Ana Ziyadatul; Munandar, Denna E; Sari, Vega K (Percetakan Umi Toaha Makassar, 2024)
Dry land is one of quite extensive marginal lands that has great potential to be developed into productive agricultural land. Limited water availability and organic matter content in dry land hamper plant adaptation, causing low dryland productivity. Combining cow dung manure as a source of organic material that is easy to obtain, able to help provide nutrients, and increase the availability of moisture and microorganisms in the soil with mustard plants which have a short harvest life and quite extensive adaptation, is expected to be an alternative solution in efforts to increase the productivity of dry land. The research aims to determine the possibility of using cow dung as a source of manure in the cultivation of green mustard on dry land. The research is based on a Randomized Complete Block Design consisting of 12 treatments with three replications. Treatments included a combination of varieties with no cow dung as a control; varieties with the addition of 10 tons ha-1 of cow dung; varieties with the addition of 20 tons Ha-1 of cow dung and varieties with the addition of 30 tons ha-1 of cow dung. The data obtained were analyzed using variance and if there were significant differences, it was continued with the HSD test at the 5% level. The research results showed that applying cow dung manure can increase the growth and yield of green mustard on dry land. The variety of Kumala showed the most adaptive response, followed by Puteri and Tosakan